The relationship between C-reactive protein to lymphocyte ratio and the prevalence of chronic kidney disease in US adults: a cross-sectional study - He, Pengfei; Zhang, Jiao; Tian, Ni; Deng, Yuanyuan; Zhou, Min; Tang, Cheng; Ma, Yu; Zhang, Mianzhi (Frontiers in Endocrinology, 2025)
ObjectiveThe C-reactive protein/Lymphocyte Ratio (CLR) is a novel biomarker whose role in the development of chronic kidney disease (CKD) is not well understood. This study aimed to investigate the correlation between CLR and the prevalence of CKD.MethodsThis cross-sectional study included participants from the US National Health and Nutrition Examination Survey conducted between 1999 and 2010. Multivariate regression analyses and subgroup analyses were performed, controlling for socio-demographic variables, lifestyle behaviors, chronic diseases associated with kidney disease, and biochemical markers of bone metabolism. The associations between CLR and CKD prevalence, as well as indicators of renal damage, were explored. Non-linear relationships were analyzed using weighted restricted cubic splines. The predictive ability of CLR for CKD was assessed by the receiver operating characteristic curve and the area under the curve was calculated. Subgroup and sensitivity analyses were conducted to validate the robustness of the model.ResultsA total of 13,862 respondents were included, comprising 2,449 CKD patients and 11,413 non-CKD patients. Weighted logistic regression modeling revealed a positive correlation between CLR levels and CKD prevalence (Odds ratio [OR] = 1.54, 95% Confidence interval [CI] = 1.30 to 1.83, P < 0.001). Additionally, CLR levels were negatively correlated with the glomerular filtration rate, a marker of renal injury, and positively correlated with the urinary albumin/creatinine ratio. The receiver operating characteristic curve demonstrated that the area under the curve for CLR in predicting CKD was 0.653 (95% CI, 0.641–0.665). The optimal cutoff value was 0.856, with a sensitivity of 0.703, specificity of 0.526, positive predictive value of 0.874, and negative predictive value of 0.275. The robustness of the model was confirmed through subgroup and sensitivity analyses.ConclusionAnalysis of a large cross-sectional dataset demonstrated a positive correlation between CLR levels and CKD prevalence, suggesting that CLR may serve as a novel marker for the development and treatment of CKD.